2018
DOI: 10.3889/oamjms.2018.175
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Knowledge and Practices of Male Adolescents in West of Iran

Abstract: BACKGROUND:Every year many people around the world become infected with food-borne infections. Insufficient knowledge and skills related to food safety and hygiene are among the factors affecting the incidence of food-borne diseases, especially in adolescents.AIM:The purpose of this study was to determine the knowledge and practices associated with food safety and hygiene in Ilam city male adolescents.MATERIAL AND METHODS:Three hundred and eighty of male adolescents aged 13 to 19 were selected randomly and ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Simultaneously, family members also gave equal credence to both genders, although females are frequently considered better than males in food handling. Recently, males have also been proven to have good knowledge and practices regarding food safety as a result of positive influence by their parents at home (Mirzaei et al, 2018). Family support might boost the confidence of consumers to be more aware of handling the food safely.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, family members also gave equal credence to both genders, although females are frequently considered better than males in food handling. Recently, males have also been proven to have good knowledge and practices regarding food safety as a result of positive influence by their parents at home (Mirzaei et al, 2018). Family support might boost the confidence of consumers to be more aware of handling the food safely.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that the improvement of people's knowledge on COVID-19 can increase their preventive behaviors for the disease. However, often high knowledge alone does not lead to optimal practice [32]. The prevention and control of COVID-19 are desirable when in addition to sufficient knowledge; there should be a favorable attitude toward preventive measures against this disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studi menunjukkan bahwa adanya hubungan positif dan signifikan antara pengetahuan dan praktik keamanan pangan (r= 0.122; p= 0.018) (Mirzaei et al 2018). Saat ini penelitian mengenai perubahan pengetahuan dan perilaku keamanan pangan selama pandemi hanya terfokus pada masyarakat secara umum yang mengkaji mengenai kesiapan makan di luar rumah dan layanan pesan antar makanan.…”
Section: Pendahuluanunclassified